RISET REAKTIFITAS LIMONIT SOROAKO SEBAGAI KATALIS PADA PENCAIRAN BATUBARA DENGAN GAS FLOW TYPE REACTOR - Herman Hidayat; Lambok Hlarius Silalahi (Jurnal Energi dan Lingkungan (Enerlink), 2006)
B r o w n Coal Liquefaction (BCL) process had been developed through theconstruction and the operation of 50 T/D pilot plant Ill Australia (1985-1990) byKOBE STEEL Group. After the successful completion of the Pilot Plant Project,newly Improved BCL process has been developed1). The feasibility study onthe commercialization of coal liquefaction plant in Indonesia has also beencarried out under the cooperation with BPPT supported by NEDO Limonitore (Î±-FeOOH) can be used as an industrial catalyst for direct coal liquefactionwith its high activity and low production cost. In this paper, the catalytic activitiesof Indonesian limonit ore, Soroako Limonit were examined using a gas flow typeautoclave comparing with the other iron catalysts for the liquefaction ofIndonesian brows coal. It appeared that the Soroako limonit has a highcatalystic activity while finely pulverizing to sub-micron particle size can bedone economically. It can be concluded that Soroako limonit is one of mostsuitable catalysts for the coal liquefaction plant constricted in Indonesia in thefut-ure.Kata kunci: direct liquefaction, soroako limonit, iron catalyst, phyrrotite, bankocoal